Human Rights Activism and the End of the Cold War : a Transnational History of the Helsinki Network. - Snyder, Sarah B. (Human rights in history., 2011)
Explores how a network of human rights activists emerged post-1975, and over time fundamentally reshaped East-West diplomacy.